2006
DOI: 10.1016/j.biocon.2006.04.006
|View full text |Cite
|
Sign up to set email alerts
|

European bat lyssaviruses: Distribution, prevalence and implications for conservation

Abstract: Surveillance European bat lyssavirus Rabies Zoonoses Conservation A B S T R A C T Worldwide, there are more than 1100 species of the Order Chiroptera, 45 of which are present in Europe, and 16 in the UK. Bats are reservoirs of, or can be infected by, several viral diseases, including rabies virus strains (in the Lyssavirus genus). Within this genus are bat variants that have been recorded in Europe; European bat lyssavirus 1 (EBLV-1), European bat lyssavirus 2 (EBLV-2) and, four currently unclassified isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 106 publications
2
45
0
Order By: Relevance
“…This also seems to be concordant with the relatively low genetic diversity of EBLV-1 across Europe possibly promoted by its host's movement . We also suggest that the English Channel, while apparently restricting some gene flow, does not appear to be a substantial barrier, and similar inferences have been drawn for M. daubentonii (Atterby et al, 2010), which is the host for EBLV-2, a virus found both on the continent and in the United Kingdom (Harris et al, 2006). The relative fragmentation of serotine populations in England may sufficiently alter host-virus epidemiology to explain the apparent absence of EBLV-1 in England.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…This also seems to be concordant with the relatively low genetic diversity of EBLV-1 across Europe possibly promoted by its host's movement . We also suggest that the English Channel, while apparently restricting some gene flow, does not appear to be a substantial barrier, and similar inferences have been drawn for M. daubentonii (Atterby et al, 2010), which is the host for EBLV-2, a virus found both on the continent and in the United Kingdom (Harris et al, 2006). The relative fragmentation of serotine populations in England may sufficiently alter host-virus epidemiology to explain the apparent absence of EBLV-1 in England.…”
Section: Resultssupporting
confidence: 68%
“…This basic information on serotine biology is particularly important as this bat is the main reservoir for the most common European bat lyssavirus, EBLV-1 (Harris et al, 2006). In such a context, knowledge of the host's movement, mating patterns and social organisation is crucial to gain further understanding of viral dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…EBLV-1 and EBLV-2 have been shown to have a specific association with the Serotine bat (Eptesicus serotinus and Eptesicus isabellinus) (Vazquez-Moron et al, 2008;Picard-Meyer et al, 2004b) and the species of Myotis bats (Myotis daubentonii and Myotis dascyneme), respectively (Whitby et al, 2000;Johnson et al, 2003;Harris et al, 2006), whereas rabies cases due to EBLVs in other bat species have only occasionally been reported (Müller et al, 2007). West Caucasian bat virus (WCBV), a recently ratified member of the lyssavirus genus with distinct genetic and biological properties, was isolated from a Schreiber's long-fingered bat (Miniopterus schreibersii) on the European side of the Caucasus mountain range (Kuzmin et al, 2005).…”
Section: Recommendations On Bat Rabies Surveillancementioning
confidence: 99%
“…We report 2 documented cases of natural infection of domestic cats by EBLV-1 lyssaviruses presently circulating in European bats (2)(3)(4)(5). Our study demonstrates that subtypes EBLV-1a and EBLV-1b can cross the species barrier, although cat no.…”
Section: Discussionmentioning
confidence: 79%
“…2 died with neurologic signs compatible with rabies and was positive for EBLV by FAT, the reference technique. Direct transmission of EBLV-1 from bats to cats seems the most realistic explanation for these cases because cats prey on bats and have numerous contacts with them (3,12,13). Identifi cation of a highly homologous EBLV-1a isolate from a rabid bat found in the same location as cat no.…”
Section: Discussionmentioning
confidence: 99%